Numerical study on the combustion and emissions characteristics of liquid ammonia spray ignited by dimethyl ether spray - Leng, Yupeng; Dai, Liming; Wang, Qian; Lu, Jiayu; Yu, Ouqing; Simms, Nigel J. (MDPI, 2024)
Ammonia has attracted considerable attention as a zero-carbon fuel for decarbonizing energy-intensive industries. However, its low reactivity and narrow flammability limit efficient ignition and efficient combustion. By using CONVERGR software, this study numerically investigates the ignition and combustion characteristics of liquid ammonia spray ignited by dimethyl ether spray in a constant-volume chamber at an ambient temperature of 900 K. Critical parameters, including injection angles (90°–150°), liquid ammonia injection pressures (60–90 MPa), and ambient pressures (2.8–5.8 MPa), were systematically analyzed to evaluate their effects on ignition conditions and emissions. Results indicate that increasing the injection angle improves mixing between liquid ammonia and dimethyl ether sprays, enhancing combustion efficiency and achieving a maximum efficiency of 92.47% at 120°. Excessively large angles cause incomplete combustion or misfire. Higher liquid ammonia injection pressures improve atomization and promote earlier interactions between the sprays but reduce combustion efficiency, decreasing by approximately 2% as injection pressure increases from 60 MPa to 90 MPa. Higher ambient pressures improve combustion stability but decrease ammonia combustion efficiency. Post-combustion NO emissions at 5.8 MPa are reduced by 60.48% compared to 3.8 MPa. The formation of NO is strongly correlated with the combustion efficiency of liquid ammonia. A higher combustion rate of liquid ammonia tends to result in elevated NO. Based on these findings, an injection angle of 120°, an NH3 injection pressure of 75 MPa, and an ambient pressure of 3.8 MPa are recommended to optimize combustion efficiency.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 41 Environmental Sciences; 3007 Forestry Sciences; 13 Climate Action; 7 Affordable and Clean Energy; 3007 Forestry sciences; 4102 Ecological applications; 4104 Environmental management; ammonia; dimethyl ether; high-pressure direct injection; ammonia ignition enhancement